Role of heat shock in building up proteins HSP70 , HSP90, increasing anthocyanins content in callus of strawberry Fragaria ananassa Duch. - Waad Al-Hamdani (Mesopotamia Journal of Agriculture)
This study was conducted in the genetic applications laboratories of University of Mosul, College of Education for Pure Sciences. Heat shock proteins HSPs were constructed for increase of withstand long-term physical shocks, and production of resistant to heat strawberry plants, The results of the study showed the production of callus cultures after two months of cultivation on Murashige and Skoog (MS) medium + 1.0, 2.0, 3.0 and 4.0 mg/L of 2 , 4 – Dichlorophenxy Acetic Acid ( 2,4-D) + 6 Benzyl adenine (BA) (1.0 mg/L). Also, a-Naphthalene Acetic Acid (NAA) was used in the same previous concentrations with BA, and the medium MS + 4.0 mg/L of 2 ,4-D + 1.0 mg/L of BA outperformed the rest of the concentrations in inducing callus, after 16 days of culture. The callus was yellow-brown color. One-month-old callus samples were exposed to short term heat shock represented by 10 minutes, and the long term which is 20 minutes at temperatures of 35, 40, 45 and 50°C. The result indicate an increasing of fresh weights,, protein , and anthocyanin . The results concluded that the 45°C for 30 min shock encouraged also protein content at the 30-day age stage, while anthocyanin pigment decreased in the same period. The current study succeeded in detecting the expression of heat shock genes HSP70 and HSP90 using RT- PCR, The results demonstrated an increase in gene activity with an increase in the severity of heat shock when callus cultures were exposed to shock 45°C / 30 min